Benazir Bhutto From Prison to Prime Minister - Hughes,Libby (U.S.A iUniverse, 2000)
This biography of Pakistan's only woman prime minister to be elected twice describes her childhood in Karachi and her university years at Harvard and Oxford. The jails and homes of her arrest during ten years are covered in vivid detail as well as her arranged marriage and political leadership.
Keywords: Prime Minister- Pakistan; Biography; Benazir Bhutto